Development and Validation of Interactive E-Learning Materials in Science 5 - ACANTILADO, MARTIN (Studies in Technology and Education, 2025)
This study aimed to develop and validate eight interactive e-learning materials for Grade 5 Science in Flora, Apayao, with the goal of enhancing student learning, improving curriculum implementation, and addressing local educational gaps. Guided by the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, the process involved the systematic design and refinement of the materials. A quantitative research design was employed to assess the effectiveness of the outputs, with ten evaluators—comprising Science teachers, master teachers, and school heads—serving as expert panelists. The evaluation focused on three key categories: learning environment, teaching-learning process, and learning assessment. Results indicated a high overall mean score of 4.48, suggesting strong agreement among experts regarding the effectiveness, usability, and learner engagement provided by the materials. These findings affirm the significant potential of the developed e-learning materials to improve conceptual understanding, foster student motivation, and elevate the quality of science instruction in the basic education setting.